Simple Evaluation of Clinical Situation and Subtypes of Pediatric Hemophagocytic Lymphohistiocytosis by Cytokine Patterns - Xu, Xiao-Jun; Luo, Ze-Bin; Song, Hua; Xu, Wei-Qun; Henter, Jan-Inge; Zhao, Ning; Wu, Meng-Hui; Tang, Yong-Min (Frontiers in Immunology, 2022)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rapidly fatal disease caused by immune-dysregulation. Early initiation of treatment is imperative for lifesaving. However, the approach that could be used to quick evaluate HLH subtype and clinical situation is lacking. Our previous studies indicated that cytokines such as interferon (IFN)-γ and interleukin (IL)-10 were helpful for the early diagnosis of HLH and were associated with disease severity. The purpose of this study is to clarify the different cytokine patterns of various subtypes of pediatric HLH, and to investigate the role of cytokines in simple evaluation of disease feature. Patients and Methods: We enrolled 256 pediatric patients with newly diagnosed HLH. The clinical features and laboratory findings were collected and compared among different subtypes of HLH. A model integrating cytokines was established to stratify HLH patients with different features and outcomes. Results: Twenty-seven patients were diagnosed with primary HLH (pHLH), 179 with EBV-HLH and 50 with other causes. The IL-6, IL-10 and IFN-γ levels and the ratios of IL-10 to IFN-γ were different among EBV-HLH, infection-associated HLH, malignancy-associated HLH, familial HLH and X-linked lymphoproliferative disease. Patients with the ratio of IL-10 to IFN-γ >1.33 and the concentration of IFN-γ≤ 225pg/mL was considered to have pHLH, with a sensitivity of 73% and a specificity of 84%. A four-quadrant model based on the two cut-off values was established to stratify the patients into different clinical situations. The HLH subtypes, cytokine levels, treatment regimens, treatment response and outcomes were different among the four quadrants, with the 8-week mortality from 2.9±2.9% to 21.4±5.5% and the 5-year overall survival from 93.9±4.2% to 52.6±7.1% . Conclusions: Different subtypes of HLH present distinct cytokine patterns. IFN-γ and the ratio of IL-10 to IFN-γ are helpful tools to differentiate HLH subtypes. A four-quadrant model based on these two parameters is a useful tool for simple evaluation of HLH situation.